Modeling of the dielectric properties of trabecular bone samples at microwave frequency - Irastorza, Ramiro Miguel (2014)
In this paper, the dielectric properties of human trabecular bone are evaluated under physiological condition in the microwave range. Assuming a two components medium, simulation and experimental data are presented and discussed. A special experimental setup is developed in order to deal with inhomogeneous samples. Simulation data are obtained using finite difference time domain from a realistic sample. The bone mineral density of the samples are also measured. The simulation and experimental results of the present study suggest that there is a negative relation between bone volume fraction (BV/TV) and permittivity/ conductivity: the higher the BV/TV, the lower the permittivity/ conductivity. This is in agreement with the recently published in vivo data.